TYPO-MORPHOLOGY OF SUDIMORO COFFEE SHOP AREA IN MALANG (International Conference of Graduate School on Sustainability (ICGSS), 2020)
TYPO-MORPHOLOGY OF SUDIMORO COFFEE SHOP AREA IN MALANG CITYSpatial and Sociological Approaches to Urban Area DevelopmentRully Bayuadhi 1), Respati Wikantiyoso 2), Tonny Suhartono 3)1)Magister of Architecture Student, University of Merdeka Malang2) Professor at the Master of Architecture Study Program, University of Merdeka Malang3) Senior Lecture at the Master of Architecture Study Program, University of Merdeka MalangAbstractThe study of coffee culture and discussing the philosophy of coffee, changes in coffee (drinking coffee), even the development of a typology of coffee shop forms. The development of coffee shops greatly affects changes in lifestyle, characteristics, or social strata of coffee drinkers, influencing the emergence of various coffee shop typologies and new coffee shops. The emergence of several coffee shops in the Sudimoro area forms the character and pattern of developing the Sudimoro area into a Coffee Shop Area (CSA). The problem is the typology of coffee shops developed in the Sudimoro area and the development pattern of CSA Sudimoro. This study aims to analyze the morphological typology of coffee shops in the Sudimoro area of ​​Malang City to obtain the morphological characteristics of coffee shops and development trends in the Sudimoro area. Data collection methods used were observation, spatial data analysis, and qualitative data. The results of this study are to determine the typical morphology of the Sudimoro area and the factors that influence the development of CSA Sudimoro and how it affects the development of the surrounding area. This study will be used as input for local governments to control the development of the Sudimoro Malang area.Keywords: Coffee Shop Typology, Regional Morphology, Sudimoro Area Morphology Typology